28-Day-Old Male With Non-Obstructing Supracardiac Total Anomalous Pulmonary Venous Connection and Atrial Septal Defect Presenting With Pulmonary Overcirculation - Ronald Van Ness-Otunnu; Leo Kobayashi; Sara Regan Ford; Frank Overly (Association of American Medical Colleges, 2012)
Abstract In populations with excellent prenatal care and sonographic fetal assessment during pregnancy, congenital heart defects are often identified, referred to, and managed by pediatric cardiologists or surgeons before delivery. Minor cardiac abnormalities may not be readily identified on ultrasound evaluation initially, but with adequate primary care, symptomatic patients or those with abnormal examination findings may be identified early and referred to an appropriate specialist. The typical presentation of a pediatric patient with congenital heart disease to the emergency department is one with an acute exacerbation of a known underlying problem. At risk, however, are those patients who do not receive timely prenatal care and those with significant, undetected cardiac abnormalities who present acutely to the emergency department, as the current case exemplifies. This simulation teaching case is intended to train the emergency medicine or pediatric resident or fellows, or critical care fellows, to rapidly assess and manage a critically ill infant with a congenital heart disease (CHD), in this case, total anomalous pulmonary venous connection (TAPVC). Participants will be expected to interpret the available data, including the electrocardiogram, laboratory results, chest radiograph, physical exam signs/symptoms, and hyperoxia test, and conclude that the infant has some form of congenital heart disease and is in a state of pulmonary overcirculation or congestive heart failure. They are not expected to specifically diagnose TAPVC. The significance of this particular variant, a nonobstructing supracardiac type with concurrent atrial septal defect will be discussed in a debriefing lecture. A treatment plan will be expected to address pulmonary edema, which may occur in conjunction with the consultation of a pediatric cardiologist. The case ends after endotracheal intubation, treatment with furosemide, and cardiology consultation are completed. This pediatric simulation case highlights clinical testing to distinguish between pulmonary and cardiac disease, and appropriate management steps to stabilize a critically ill infant in the team environment of a pediatric emergency critical care room. Although cases of TAPVC are uncommon, broader skills are reviewed in this patient encounter that include stabilizing airway, breathing, and circulation in a critically ill infant and recognizing the manifestation of a congenital heart disease and initiating emergency management.